+0

# Help. ​

0
59
1
+1159

Help.

NotSoSmart  Nov 20, 2017
Sort:

#1
+5586
+2

1.   4x3 + 8x2 - 96x

Factor  4x  out of each term.

=    4x(x2 + 2x - 24)

Factor  x2 + 2x - 24  as  (x - 4)(x + 6) .

=  4x(x - 4)(x + 6)

(The one you have selected is right.    )

3.     We want to solve this equation for  x :

0  =  x4 - 4x3 + 3x2

Factor  x2  out of all the terms on the right side.

0  =  x2(x2 - 4x + 3)

Factor  x2 - 4x + 3  as  (x - 1)(x - 3) .

0  =  x2(x - 1)(x - 3)

And we can "factor"  x2  as  x * x .

0  =  (x)(x)(x - 1)(x - 3)

Set each factor equal to zero and solve for  x .

x  =  0       or       x  =  0       or       x  =  1       or       x  =  3

x  =  0  occurs twice, so it has multiplicity  2 .

x  =  1  occurs once, so it has multiplicity  1 .

x  =  3  occurs once, so it has multiplicity  1 .

hectictar  Nov 20, 2017
edited by hectictar  Nov 20, 2017

### 20 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details